The Palgrave Handbook of Sexuality Education - Allen, Louisa; Rasmussen, Mary Lou (Springer Nature, 2016)
This authoritative, state-of-the-art Handbook provides an authoritative overview of issues within sexuality education, coupled with ground-breaking discussion of emerging and unconventional insights in the field. With 32 contributions from 12 countries it definitively traces the landscape of issues, theories and practices in sexuality education globally. These rich and multidisciplinary essays are written by renowned critical sexualities studies experts and rising stars in this area and grouped under four main areas: Global Assemblages of Sexuality Education Sexualities Education in Schools Sexual Cultures, Entertainment Media and Communication Technologies Re-animating What Else Sexuality Education Research Can Do, Be and Become Importantly, this Handbook does not equate sexuality education with safer sex education nor understand this subject as confined to school based programmes. Instead, sexuality education is understood more broadly and to occur in spaces as diverse as community settings and entertainment media, and via communication technologies. It is an essential and comprehensive reference resource for academics, students and researchers of sexuality education that both demarcates the field and stimulates critical discussion of its edges. Chapter 2 is available open access under a CC BY 4.0 license via link.springer.com.